Sistem Informasi Pramuka Berbasis Website Menggunakan Rational Unified Process - Henri Herdiyanto; Lukman Lukman (Forum Kerjasama Pendidikan Tinggi, 2022)
In this study the authors will examine the scouting system where the system built is able to overcome various problems that exist in the scouting area, including the registration process, dissemination of activity information, money management and trainer requests. Data collection on scouting activities in the city of Sorong, West Papua is still mostly done manually, this has resulted in many files being damaged or lost. Therefore we need a system that improves services to manage data and can overcome these obstacles. The making of this scouting information system is made using the PHP programming language and MySQL for the database. The method used is the rational unified process (RUP) where in this method the steps for making a good and correct system are described as well as testing using Roger Prassman where the results of the research carried out got a 90% satisfaction level